EdTech Evidence From Covid-19 Response: A thematic review of primary research from Bangladesh, Ghana, Kenya, Pakistan and Sierra Leone - Nicolai, Susan; Jefferies, Kate; Stepanek Lockhart, Ashley (EdTech Hub, 2023)
To better understand the use of EdTech interventions as part of response to the Covid-19 pandemic, EdTech Hub commissioned ten small-scale research studies in five low- and middle-income countries: Bangladesh, Ghana, Kenya, Pakistan, and Sierra Leone. This paper includes insight into research methodologies across these studies, with particularly interesting findings on how EdTech effectiveness is being measured. A semi-structured thematic analysis further provides insights in relation to four main user groups of learners, girls, teachers, and parents and caregivers and points to a series of cross-cutting factors that are important for EdTech interventions in low-resource settings. An overarching takeaway centres on the fact that having technology in place is a small part of EdTech effectiveness, with wider teaching and learning ecosystems accompanying EdTech deserving more attention. Overall, the studies reveal a symbiotic relationship between people and technology, reinforcing that EdTech works best when users are involved across design, iteration, awareness building, and engagement. Keywords: EdTech, Covid-19, digital, education, learning, remote An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Using Technology to Improve Education for Marginalised Girls: Lessons in implementation from the Girls’ Education Challenge - Anonymised for Peer Review Purposes (EdTech Hub, 2023)
This article presents the findings of an in-depth study on the implementation of six EdTech-supported projects within the UK Government Foreign, Commonwealth and Development Office (FCDO)’s Girls’ Education Challenge portfolio, which aims to improve education for the world’s most marginalised girls. Using primary key informant interviews and secondary data from sampled projects, the study identifies the core components related to the implementation of EdTech within the sampled projects: evidence-informed design and delivery; building and maintaining relationships across and between stakeholders; comprehensive and continuous training and capacity development; and situating EdTech within a broader holistic model that prioritises gender inclusion to optimise implementation for marginalised girls. In doing so, the study provides key lessons for optimising the future implementation of EdTech for marginalised girls. Keywords: educational technology; girls’ education; programme implementation; Covid-19 An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Understanding Barriers to Girls’ Access and Use of EdTech in Kenya During Covid-19 - Tembey, Lara; Baier, Jasmin; Ogolla, Concilia; Mohan, Prithika (EdTech Hub and Busara Center for Behavioural Economics, 2021)
The Covid-19 pandemic resulted in the closure of approximately 90,000 schools across Kenya, causing over 18 million pre-primary, primary, and secondary school learners to be out of school throughout 2020. These lockdown measures of Covid-19 are expected to amplify gender inequalities in education and girls’ access to school, with girls likely to have experienced losses in learning during the pandemic to a greater extent than their male counterparts (⇡Malala Fund, 2020). To enable continued learning during this period, numerous education technology (EdTech) solutions and products have been developed to enable remote learning. This technology can be a powerful tool for girls. Studies have shown that girls engage more than boys when provided with the same level of access to technology, and receive more benefits beyond the realm of formal education such as an increase in access to economic opportunities and a greater ability to make informed decisions about their own health (⇡Webb et al., 2020). However, social inequalities, norms and technological constraints can disproportionately prevent girls from accessing and benefiting from EdTech (⇡Crompton et al., 2021). As such, EdTech interventions and products need to be designed and implemented prioritising gender considerations, otherwise they risk increasing the digital gender divide both in terms of access and use of digital technologies and the internet and the development of skills needed to use digital technologies (⇡Kuroda et al., 2019). Our qualitative and quantitative research looked at how access and usage of learning content and edutainment through smartphone and low-tech (such as radio, Interactive Voice Response, TV) EdTech solutions can be optimised to ensure inclusivity of girls, in particular, focusing on the caregiver as the gatekeeper for access to EdTech resources. In terms of access, our research found that caregivers are primarily concerned about financial resources, books and tutors, and often do not consider using EdTech to access educational resources when they are looking for support for their children. Further, our research showed that digital literacy, caregiver involvement, norms about technology for education, and intention are the most promising levers to improve access and use of educational material. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

EdTech for Contexts of Forced Displacement: A Rapid Evidence Review - Barnes, Katrina; Katrin, L (EdTech Hub, 2025)
This Rapid Evidence Review provides a synthesis of recent evidence relating to the implementation of EdTech programmes, platforms, and devices for learners in contexts of forced displacement. The main aim of the review is to provide education decision-makers, funders, and implementers (among others), with a clear picture of which interventions may be the most effective in these contexts and, crucially, which implementation decisions facilitate or hinder this effectiveness. We reviewed evidence generated between 2019 and 2024 on EdTech implementations in different contexts of forced displacement. We focused on implementations aimed at primary- and secondary-age learners, as well as their teachers and caregivers. Keywords: forced displacement, refugee education, education in emergencies An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

EdTech for Education in Emergencies: A Rapid Evidence Review - Barnes, Katrina; Ramesh Vasudevan, Sharanya; Flam, Rebekka (EdTech Hub, 2025)
This Rapid Evidence Review (RER) provides a synthesis of recent evidence relating to the implementation of EdTech programmes, platforms, and devices in emergency contexts. The main aim of the review is to provide education decision-makers, funders, and implementers (among others) with a clear picture of ‘what works’ regarding EdTech in emergencies. Crucially, it also aims to create an understanding of the conditions necessary to ensure the effectiveness of these interventions. Accordingly, the results of the review are grouped under three key themes: types of EdTech that are most effective in emergencies; barriers and challenges that limit EdTech effectiveness in emergencies; and conditions for effective implementation of EdTech in emergencies. Keywords: Education in Emergencies; EdTech; crisis contexts; remote learning An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

EdTech for Ugandan girls: Affordances of different technologies for girls' secondary education during the Covid-19 pandemic - Damani, Kalifa; Daltry, Rebecca; Jordan, Katy; Hills, Libby; Evans, Laura (Development Policy Review, 2022)
Motivation This article discusses the use of educational technology (EdTech) in girls' education at PEAS (Promoting Education in African Schools) schools in rural Uganda during the Covid-19-related school closures. Purpose This article addresses a research gap surrounding the potential use of EdTech to support girls' education, focusing on the barriers to girls' EdTech use and how technology might be used to enhance girls' education in disadvantaged rural areas—specifically their academic learning and their social and emotional learning. Methods and approach A sequential, explanatory mixed-methods case-study approach was used. Quantitative exploration of a dataset of 483 Ugandan students, from 28 PEAS schools, was first conducted, followed by interviews with PEAS staff to elucidate the reasons and context behind the findings. Findings Findings show that female students are less likely than male students to have access to their caregivers' phones for learning. The form of EdTech that appeared to be most beneficial for girls' academic learning was radio; girls also had significantly more interest in tuning into radio broadcasts than boys did. Also, poorer boys were more likely to be influenced by SMS messages than wealthier boys. Apart from gender-based differences, students with more highly educated parents found SMS messages more helpful, and phone calls from teachers appeared to help boost younger students' self-confidence. Policy implications The findings suggest that policy-makers need to: carefully consider provision of education through multiple modes of EdTech in order to ensure that it reaches all students; ensure that caregivers are involved in the strategies developed for girls' education; make EdTech interventions interactive; and consider language in EdTech interventions. Given the gender differences which emerged, the findings are of relevance both to supporting the continuation of educational provision during periods of school closure, and also in terms of finding additional ways to support girls' education alongside formal schooling.
Keywords: Covid-19; EdTech; education; gender; rural Uganda

EdTech to Support Out-of-School Children and Adolescents - Thinley, Sangay; Rui, Yang (EdTech Hub, 2023)
This Helpdesk report was created in response to a request from the World Bank Malawi Education Team for a curated list of resources on examples of EdTech interventions targeting out-of-school children and adolescents to inform an ASA (Advisory Services and Analytics) output. The ASA output will provide policy options to improve second-chance learning and foundational skills for out-of-school children (OOSC). To provide the World Bank Malawi team with adequate information on the above. This curated list begins with an introduction to the use of EdTech to support out-of-school children and youth, and then moves on to present examples of such interventions and programmes within Malawi, as well the wider African region and the rest of the world. This list is designed to serve as a resource for the team and does not make any direct recommendations on actions to be taken. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found